Сommission test of Effectiveness of the supramolecular complex based on triclabendazole and albendazole at Fasciolosis and gastrointestinal strongylatosis of sheep - E. V. Lagereva; V. E. Abramov; M. B. Musayev; Sh. V. Vatsayev; A. Z. Dzhamalova; Kh. Kh. Shakhbiyev (Российский паразитологический журнал, 2020)
The purpose of the research is a commission test of the effectiveness of the supramolecular complex based on triclabendazole and albendazole (SMCTA) against gastrointestinal nematodes and fascioles of sheep in a previously calculated therapeutic dose.Materials and methods. The SMCTA effectiveness was tested in the North Caucasus Federal District in July 2019 on Tushin sheep spontaneously infected with gastrointestinal nematodes and fascioles simultaneously. The sheep were owned by an independent entrepreneur. Coproovoscopic examinations were carried out according to the GOST by the Fulleborn’s method using ammonium nitrate at the Republican Veterinary Laboratory of Grozny. Helminthological dissection of 5 control sheep was done to determine the intensity of infection with fascioles and gastrointestinal nematodes, and 3 sheep from each group were dissected at 14 days after dehelminthization to record the effectiveness of the drug. 4 more sheep from each group were dissected on the 25th day. The drug effectiveness was recorded by the critical test method according to the Guidelines approved by the World Association for the Advancement of Veterinary Parasitology (1995).Results and discussion. When conducting clinical trials on sheep spontaneously infected with strongylates of the gastrointestinal tract and lungs, and fascioles, a therapeutic dose was calculated when the drug was administered individually in the form of a suspension of 4.0 mg/kg for the Active Substance (2.0 for ABZ : 2.0 for TCB), 40 mg/kg for the drug, and in a mixture with concentrated feed using the group method of 5.0 mg/kg for the AS (2.5 mg/kg for ABZ : 2.5 mg/kg for TCB), 50 mg/kg for the drug. The commission test of SMCTA at a dose of 5.0 mg/kg for the AS (50 mg/kg for the drug) by the group method in a mixture with combined feed at fasciolosis and strongylatosis of the gastrointestinal tract of sheep showed, according to the coproovoscopy and helminthological dissection of animals, that 100 % efficiency was obtained. A mixture of the drug with combined feed was readily eaten by the sheep; and no side effects were noted after dehelminthization. The Commission noted the absence of side effects, high efficiency and a wide spectrum of the SMKTA effect at a 4-fold reduced therapeutic dose of 5.0 mg/kg as compared with the albendazole (7.5 mg/kg) and triclabendazole (10 mg/kg) substances.